Transformation of the Socio-economic System and the Implementation of Automation Processes in Terms of Shaping Order and Sustainability Processes - Piontek, Barbara (Problemy Ekorozwoju, 2020)
This article addresses the topic of technological transformation, which is a challenge for progressing automation and robotization processes. The topic is extremely important in terms of changes in contemporary global reality. On the one hand, changes in production factors, automation and robotization processes, and changes in the labor market give rise to some fears, on the other hand, they can be a chance to build a new socio-economic order based on the pillars of sustainability. This system requires the application of the rules of universal behavior and the recognition of work as value in itself. These rules are an important recommendation and basis for shaping decisions in the sphere of choosing new order and ensuring sustainability, rather than only in consumption. The article synthesizes existing research, which was the basis for further studies and the following hypothesis has been adopted: automation and robotization processes will result in turbulence on the labor market and in the social sphere. The key purpose of this article is demonstrate that currently automation and robotization are not the subject of systemic research in the field of shaping the structural order in the economic and social sphere, to develop a scheme of technological transformation and to indicate the need to build a strategy for automation and robotization by states that will ensure strategic order and security. Today, we need to think what should be done to ensure that automation and robotization, as well as the resulting income, do not push the crowds of society into the sphere of lucky losers. Will the distribution of benefits that automation and robotization give today affect the few or all of us? Will the economy and society based on these processes retain the value of work, and will the profits generated from automation and robotics contribute to prosperity, sustainability and development? Are decision makers ready today to prepare comprehensive solutions? The answer to these questions must be formulated today, because modernity will not pass us by.